2017
DOI: 10.1038/nature20815
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental autophagy promotes tumour growth

Abstract: As malignant tumours develop, they interact intimately with their microenvironment and can activate autophagy1, a catabolic process which provides nutrients during starvation. How tumours regulate autophagy in vivo and whether autophagy affects tumour growth is controversial2. Here we demonstrate, using a well characterized Drosophila melanogaster malignant tumour model3,4, that non-cell-autonomous autophagy is induced both in the tumour microenvironment and systemically in distant tissues. Tumour growth can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
363
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(375 citation statements)
references
References 31 publications
11
363
0
1
Order By: Relevance
“…We identified IL-6, IL-8, and bFGF, known HNSCC secreted factors, are all at least in part responsible for CAF autophagy. This corroborates recent findings in a Drosophila tumor model that IL-6 secretion from the tumor promotes stromal autophagy (42). We demonstrate HNSCC secreted bFGF activates STAT3, induces the transcription of SOX2, which inhibits mTOR transcription (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We identified IL-6, IL-8, and bFGF, known HNSCC secreted factors, are all at least in part responsible for CAF autophagy. This corroborates recent findings in a Drosophila tumor model that IL-6 secretion from the tumor promotes stromal autophagy (42). We demonstrate HNSCC secreted bFGF activates STAT3, induces the transcription of SOX2, which inhibits mTOR transcription (34).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observe that primary patient-derived CAFs sustain an increased level of basal autophagy as compared to NFs from cancer-free patients. This is the first observation of enhanced fibroblast autophagy from primary CAFs-derived from patient stroma, and corroborates recent observations of breast cancer cells inducing autophagy in skin fibroblasts, and a Drosophila melanogaster tumor model where microenvironmental autophagy was observed (41,42). …”
Section: Discussionsupporting
confidence: 89%
“…Autophagy is considered to play a dual role in the process of tumor formation. A lack of autophagy genes would destroy the environmental balance and may lead to the occurrence of tumors; furthermore, autophagy can promote tumor cells resistance to stress, meaning improved survival of cancer cells (19). It is thought that autophagy is a type of anti-tumor mechanism (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is a catabolic process that provides nutrients during starvation [8]. Katheder et al reported that the microenvironmental contributes to early tumor growth through nutrient-generating autophagy [9]. Autophagy preserves cardiac structure and function under baseline conditions and is activated during stress, limiting damage under most conditions.…”
Section: Introductionmentioning
confidence: 99%